Sedimentation and soil carbon accumulation in degraded mangrove forests of North Sumatra, Indonesia - Murdiyarso, D.; Hanggara, B.B.; Lubis, A.A. (Cold Spring Harbor Laboratory, 2018)
Mangrove ecosystems are often referred to as “land builders” because of their ability to trap sediments transported from the uplands as well as from the oceans. The sedimentation process in mangrove areas is influenced by hydro-geomorphic settings that represent the tidal range and coastal geological formation. We estimated the sedimentation rate in North Sumatran mangrove forests using the210Pb radionuclide technique, also known as the constant rate supply method, and found that mudflats, fringes, and interior mangroves accreted 4.3 ± 0.2 mm yr−1, 5.6 ± 0.3 mm yr1, and 3.7 ± 0.2 mm yr−1, respectively. Depending on the subsurface changes, these rates could potentially keep pace with global sea level rise of 2.6−3.2 mm yr−1, except the interior mangrove they would also be able to cope with regional sea-level rise of 4.2 ± 0.4 mm yr−1. The mean soil carbon accumulation rates in the mudflats, fringes, and interior areas were 40.1 ± 6.9 g C m−2yr−1, 50.1 ± 8.8 g C m−2yr−1, and 47.7 ± 12.5 g C m−2yr−1, respectively, much lower than the published global average of 226 ± 39 g C m−2yr−1. We also found that based on the excess of radioactive elements derived from atomic bomb fallout, the sediment in the mudflat area was deposited since over 28 years ago, and is much younger than the sediment deposited in the interior and fringe areas that are 43 years 54 years old, respectively.